A Pediatric Patient with Severe Obstructive Sleep Apnea and Comorbid Depression and Substance Abuse - Caitlin E. Leconte; Joshua W. Ng; Ann M. Manzardo; Mitchell M. Douglass (Case Reports in Psychiatry)
Obstructive sleep apnea (OSA), depression, and substance abuse problems share similar symptomatology and have significant interplay. An underlying diagnosis of OSA can often be overlooked in patients with significant psychiatric illness and polysubstance use. Pediatric OSA is often associated with adenotonsillar hypertrophy and frequently requires surgical intervention for resolution of symptoms. Untreated OSA can worsen mental status and encourage polysubstance abuse as a form of self-medication. Proper identification and management of OSA plays an important role in treating psychiatric conditions. We report a 16-year-old with major depressive disorder (MDD), suicide attempts, polysubstance use disorder, and severe OSA admitted to an inpatient psychiatric facility. History included sleep and mood disturbances started at age 12. Patient presented with apnea–hypopnea index greater than 50 and started on bilevel-positive airway pressure (BiPAP) prior to admission. Management of OSA led to significant improvement of MDD, insomnia, and polysubstance abuse. OSA can often be overlooked in patients with MDD or substance abuse. Among adolescent patients with poorly managed psychiatric conditions, significant sleep disturbances, and polysubstance abuse, providers should maintain a high degree of suspicion for OSA, as its proper management will aid in the management of the other conditions.